Performance following convertible bond issuance - Lee, Inmoo; Loughran, Tim (Journal of Corporate Finance, 1998)
Using a sample of 986 convertible bond issuers of U.S. operating companies during 1975–1990, we document poor stock and operating performance in the years following the offering. The underperformance of stock returns cannot be explained by new issues activity (recent initial public offerings (IPOs) or seasoned equity offerings (SEOs)) or the level of the proceeds. Concurrent with the low subsequent stock returns, we document a rapid decline in the operating performance of the issuers following the offering. Profit margin and return on assets for the issuers are approximately halved in the four years after the convertible bond issue.